The Strategic Role of Forecasting in Managerial Planning: A Scientific Literature Review - Sutriana, Ria Ayu Widari; Sudirman, I Made Surya Negara (The Journal of Financial, Accounting, and Economics, 2024)
This study aims to systematically review the academic literature related to the role of forecasting in managerial planning, using the Systematic Literature Review (SLR) approach. This review was conducted on 47 articles published between 2015 and 2024, collected from reputable databases such as Scopus and Web of Science. The focus of the study includes methodological approaches, key findings, research trends, and geographical and sectoral distribution of the analyzed studies. Following the PRISMA protocol, this study successfully identified key topics such as prediction accuracy, forecasting applications in strategic decision making, and challenges in applying forecasting in a dynamic business environment. The benefits of this study include strengthening the theoretical and practical foundations in forecasting for more accurate and objective decision-making. Academics can use the study results as material for curriculum development and further research directions, while practitioners obtain guidance in strategically implementing forecasting. This study also fills the gap in the literature related to the integration of forecasting theory and practice. It contributes to educating organizations to shift from an intuitive approach to a data-driven approach in future planning.